Locus of Control to Improve Student Work Readiness (Evaluation of affective, cognitive and psychomotor aspects) - Mochamad Cholik; Soeryanto Soeryanto; Tri Rijanto; I Made Arsana; Diana Nur Azizah (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2022)
This study intends to find variable interrelationships: control locus, work readiness and evaluation of cognitive, affective and psychomotor aspects in students of vocational school electrical installation engineering expertise program in Mojokerto City.. This research is an ex post facto data collection technique with locus of control variable questionnaire, work readiness variables covering three domains namely job readiness reviewed cognitive learning results using tests, work readiness reviewed affective realm learning results using questionnaires and work readiness reviewed psychomotor learning results using performance tests The results of this study have a positive and significant strong attachment between variable locus control and work readiness (with a value of sig. 0,000 reviewed from the learning outcomes of the cognitive realm, with a value of significant 0,000 reviewed from the results of learning affective realm and with a value of sig. 0.000 reviewed from the learning results of the psychomotor realm.